Implementation of Bus Rapid Transit in Copenhagen: A Mesoscopic Model Approach - Ingvardson, Jesper Bláfoss; Jensen, Jonas Kornerup (Proceedings from the Annual Transport Conference at Aalborg University, 2012)
Bus Rapid Transit (BRT) has shown to be an efficient and cost-effective mode of public transport, and has gained popularity in many cities around the world. To optimise the operations and infrastructure it is advantageous to deploy transport models. However, microscopic models are very inefficient for large scale corridors due to the vast amount of data and resources required. Hence, it is relevant to investigate how to model and evaluate BRT efficiently. In this paper the effects of implementing BRT in Copenhagen is discussed including how to evaluate and model bus operations. For this purpose, a mesoscopic simulation model is developed. In the model bus operations are modelled on a microscopic level whereas the interactions with other traffic are modelled macroscopically. This makes it possible to model high-frequency bus services such as BRT lines in more details without the time consumption of micro-simulation models. The developed model is capable of modelling bus operations in terms of travel time and reliability including important mode-specific issues such as bus bunching. The model is applied to a BRT project proposal with different combinations of BRT elements. The model results show that infrastructure upgrades (busways and enhanced stations) ensure a reduction to travel time whereas no improvements to reliability occur. Upgrades to technology and service planning (pre-paid fare collection, boarding and alighting from all doors, special BRT vehicles, ITS, and active bus control) ensure an increase in service reliability whereas only small reductions to travel time are observed. By combining all BRT elements it is possible to obtain synergies where the improved reliability due to planning and technology elements makes it possible to utilise the infrastructure optimally. Hence, it is possible to increase commercial speed from 14.8 to 19.9 km/h and service reliability in terms of headway time regularity from 46% to 84% aggregated on both directions for the morning peak period making the implementation of BRT feasible from a pure financial point of view.